Long-term labour productivity and GDP projections for the EU25 Member States : a production function framework - Carone, Giuseppe; Denis, Cecile; Mc Morrow, Kieran; Mourre, Gilles; Roger, Werner; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
This paper presents the results of long run labour productivity and GDP growth rate projections (until 2050) for each of the 25 EU Member States and provides a detailed overview of the forecast methodology used. These projections were undertaken in order to provide an internationally comparable macroeconomic framework against which to assess the potential economic and fiscal effects of ageing populations. This assessment was carried out as part of the work undertaken by the EU's Economic Policy Committee, in its Ageing Working Group, to project the public expenditure implications of ageing on pensions, health care, long-term care, unemployment insurance and education. The projections presented in this paper, using a common production function methodology for all 25 countries, show the GDP growth rate effects of an assumptions-driven extrapolation of recent trends in employment and labour productivity. These base case projections reflect the working assumption of "no policy change" and should not therefore be seen as forecasts of long run sustainable rates of growth but more as an indication of likely developments if past trends were to persist in the future. In overall terms, the EU25 baseline projection suggests a significant slowdown in potential growth rates in the Union as a whole, with the EU25 growth rate projected to fall from around 2 ½ % at present to half that rate over the period 2041-2050. While the decline in the growth rate of living standards is less dramatic, it is nevertheless significant, with EU25 GDP per capita growth rates expected to decline from 2 ¼ % at present to 1 ½ % in the 2040's. Finally, various sensitivity tests are carried out to check the GDP per capita impact of some factors which have been excluded from the baseline scenario for reasons of simplicity or because of a lack of consensus in the academic literature. Some of the interesting conclusions that emerge from these sensitivity tests include : • Firstly, the GDP per capita impact of changes in the participation rate assumption used in the projections is much greater than for assumed changes in the share of part-time employment (i.e. in average hours worked per worker). • Secondly, the negative effect of a change in the age-structure of the population is fairly limited, although it is accepted that the labour productivity of an individual is likely to decline after the age of 55. A very strong fall in the productivity of older workers compared with that of prime-age workers would be required to significantly depress total labour productivity. Such an outcome, on the basis of current evidence, appears rather unlikely. • Thirdly, changing the TFP growth rate targets (e.g. use of the 1990's average instead of the long-term 1970-2004 average) could strongly affect the projections. • Finally, an assumption of productivity convergence in levels substantially alters the projections for most EU10 countries but leaves the EU15 almost unchanged.
Economic Papers